Patty's industrial hygiene. Volume 2. - Cohrssen, Barbara (Wiley, 2021)
"Patty's Industrial Hygiene has had a reputation for the past 60 years of providing up to date information for the experienced as well as novice industrial hygienist. The field of IH continues to change with personnel often working for multinational firms, self-employed, or at small consulting firms. In the current era industrial hygiene not only have to worry about occupational health and safety concerns of global workforce that is more diverse, they often have to provide environmental health information for large companies, and both large and small government agencies. In response to these changes the 7th edition of Patty's Industrial Hygiene both adds new industrial hygiene/safety topics and update existing ones. The new edition addresses the needs brought about by globalization and the need for many professionals to expand their roles. The 7th edition has put in place a diverse editorial board from different regions of the world, insuring that it has a worldwide group of contributors, and covers topics of interest globally. In addition environmental topics have been added to coordinate with the American Industrial Hygiene Association's initiative to recognize the ever expanding role of industrial hygienist. Quoting Harry Elston, editor of Journal of Chemical Health and Safety, "'Patty's.' Enough said. The name has a golden reputation associated with it.""--